Realistic simulation: use and benefits for teaching - learning nursing diagnostic reasoning (Research, Society and Development, 2020)
Objective: to evaluate the use of students' learning about nursing diagnostic reasoning, through realistic simulation. Methodology: cross-sectional study, with a quantitative approach, developed at a public university in Northeast Brazil with students from the last year of the Nursing Undergraduate Course. For the evaluation, the students answered an evaluation instrument on realistic simulation with 11 questions, using a 5-point Likert scale. The ethical principles of research with human beings were respected. Results: the evaluation of the students' learning performance presented higher means (5.0) for the following items: simulation as a teaching-learning strategy, made it possible to develop the diagnostic reasoning, made it possible to develop the clinical judgment, recommend the realistic simulation for teaching the graduation and lowest average (3.87) for the item adequate time. Conclusion: The study identified that students usefully evaluated learning about nursing diagnostic reasoning, through realistic simulation. Realistic simulation presents itself with a teaching strategy for the development of nursing diagnostic reasoning and clinical judgment for bringing theory and practice closer together, contributing to the formation of critical and reflective professionals better prepared to act on current everyday problems.